The urgency of Polya model problem-solving on students mathematical ability in facing the Industrial Revolution 5.0 - Abdurrahman Al Kayyis; Mohammad Tohir; Muhasshanah Muhasshanah (Alifmatika (Jurnal pendidikan dan pembelajaran Matematika), 2024)
In the millennial era, most students consider mathematics a difficult subject, so mathematics can be a scary threat to them when this subject takes place. Conditions like this occur for two reasons: problem-solving is difficult, or they get an educator who is usually called a killer. This research aims to teach students that difficult mathematics problems can be solved using the Polya model. The research method used is qualitative, with technical data collection in interviews, questionnaires, tests, and observations. The data analysis was done using the Miles and Huberman models. There were 16 High School students, Ibrahimy Sukorejo, who were the subjects of this research to provide research results on the urgency of using the Polya model. The research results show that (1) The test results of students using the Polya model were obtained for the categories of very critical (12.5%), critical (12.5%), quite critical (37.5%), less critical (18.75%), and not critical (18.75%); (2) the results of the analysis using Shapiro-Wilk on SPSS software showed that the research had a normal distribution because the final significance results were 0.823 and 0.998 > 0.05; and (3) the results of the analysis also show the advantages felt by Polya model users over non-Polya models. There is great hope for students, especially in mathematics, who can apply the Polya model to every mathematical problem they face to find answers to these problems and a systematic way of thinking to solve them.